Activating the cognitive learning activity through “Dead” case - Vitchenko, Andrii O.; Vitchenko, Anastasiia Yu.; Izhutova, Iryna V.; Aleksandrova, Loryna G.; Romaniuk, Viktoriia L. (Linguistics and Culture Review, 2021)
The authors investigated technologization of educational process in high school and formation of interactive communicative environment for professionally oriented learning. Analysis of the problems of cases use in modern teaching practice was conducted. Methods of questionnaires, empirical data generalization, theoretical analysis of case study, justification of approaches to its technological effectiveness, “dead case”, findings generalization, defining prospects of further problem consideration were used. The authors identified the features of case study technological implementation and developed the “dead” case-based study algorithm for development of future lecturers’ professional skills. The conditions of the effective use of case technology in high school were defined. The authors proved the integral character of the case technology.